PEDF-induced alteration of metabolism leading to insulin resistance - Carnagarin, Revathy; Dharmarajan, Arunasalam; Dass, Crispin (Elsevier Ireland Ltd, 2015)
Pigment epithelium-derived factor (PEDF) is an anti-angiogenic, immunomodulatory, and neurotrophic serine protease inhibitor protein. PEDF is evolving as a novel metabolic regulatory protein that plays a causal role in insulin resistance. Insulin resistance is the central pathogenesis of metabolic disorders such as obesity, type 2 diabetes mellitus, polycystic ovarian disease, and metabolic syndrome, and PEDF is associated with them. The current evidence suggests that PEDF administration to animals induces insulin resistance, whereas neutralisation improves insulin sensitivity. Inflammation, lipolytic free fatty acid mobilisation, and mitochondrial dysfunction are the proposed mechanism of PEDF-mediated insulin resistance. This review summarises the probable mechanisms adopted by PEDF to induce insulin resistance, and identifies PEDF as a potential therapeutic target in ameliorating insulin resistance.